Flowering Phenology and the Influence of Seasonality in Flower Conspicuousness for Bees - Martins, Amanda Eburneo; Camargo, Maria Gabriela Gutierrez; Morellato, Leonor Patricia Cerdeira (Frontiers in Plant Science, 2021)
Flowering patterns are crucial to understand the dynamics of plant communities reproduction and resource availability for pollinators. Seasonal climate constrains flower and leaf phenology, where leaf and flower colors likely differ between seasons. Color is the main floral trait for pollinators attraction, however, seasonal changes in the leaf-background coloration affects the perception of flower color contrasts by pollinators. For a seasonally dry woody cerrado community (Brazilian savanna) mainly pollinated by bees, we verified whether seasonality affects flower color diversity over time and if flower color contrasts of bee-pollinated species differ between seasons due to changes in the leaf-background coloration thus enhancing flower conspicuity. We classified flower colors for 140 species based on human-color vision and for 99 species based on bee-color vision (spectral measurements). We described the community flowering pattern according to the flower colors using a unique 11-year phenological database. For 43 bee-pollinated species with reflectance data, we compared flower color diversity and contrasts against the background between seasons, considering the background coloration of each season. Flowering was markedly seasonal, peaking at the end of the dry season (September), when the highest diversity of flower colors was observed. Yellow flowers were observed all year-round, while white flowers were seasonal, peaking during the dry season and pink flowers predominated in the wet season, peaking in March. Bee-bluegreen flowers peaked between September and October. Flowers from wet and dry seasons were similarly conspicuous against their corresponding background. Regardless of flowering season, the yellowish background of the dry season promoted higher flower color contrast for all flower species, while the wet season greener background promoted a higher green contrast. Temporal patterns of flower colors and color contrasts were related to the cerrado seasonality, and likely bee activity, visual system, and behavior. Background coloration influenced flower contrasts, favoring flower conspicuousness to bees according to the season, provide new insights regarding the temporality of plant-pollination interactions.